ANALISA SARANA PENYEBERANGAN DAN PERILAKU PEJALAN KAKI MENYEBERANG DI RUAS JALAN IR. H. JUANDA KOTA JAMBI - Fakhrul Rozi Yamali; Ari Setiawan; Muhamad Fikry Ari Prasetyo; Fakhrul Rozi Yamali (Universitas Kristen Maranatha, 2022)
Road users are an important part of the government's attention. Road users have the right to the availability of supporting facilities in the form of sidewalks, crossing places and other facilities.Road users must get the main attention when crossing the road on the crossing, and in the absence of the facilities referred to earlier, the user the road has the right to cross at the place chosen by paying attention to their safety. The analysis is carried out by adding up the volume of pedestrians and adding up the traffic volume to choose the appropriate means and meet the requirements at the location. The measuring steps used to select the means of crossing are the volume of pedestrians and traffic, vehicle speed, headway time, road user speed, road capacity, and degree of saturation. The survey runs in three days, namely working days, namely Mondays and Thursdays, and holidays, namely Saturdays. From the data analysis in the field, it can be concluded why the research location requires a pelican cross crossing facility, because all measurements fulfill the requirements to build the crossing to support comfort, safety, and smooth road flow at the site.